When Fieldwork Ends: Navigating Ongoing Contact with Former Insurgents - Albanus, Rachel Sophia (Terrorism and political violence, 2021)
In research on terrorism and political violence, “fieldwork” now means many things. Scholars conduct interviews online, meet former extremists in urban centers, and travel across the globe to interview ex-combatants. But in this world of social media and constant connectivity, it is no longer possible to fully leave the “field.” Complicating matters is that researchers often do not speak openly about the ethical dilemmas they face—both during and after fieldwork—fearing it might damage their credibility. While various scholars have explored the ethical complexities of fieldwork in conflict-affected areas, there has been little discussion in political science on ethical challenges after fieldwork, and even less on how these post-fieldwork experiences are often highly gendered. Once fieldwork is over, what challenges do researchers face, what are researchers’ obligations to participants, and what types of regulations guide this behavior—especially when participants are former violent actors? What are the power dynamics between researchers and participants, how does gender affect these dynamics, and how do these relationships guide future interactions? For example, how do researchers deal with post-fieldwork requests for money or assistance? And how do scholars decide what to publish, and when, if they have received threats, or if threats to their participants change? Based on my experiences conducting over hundred interviews across Colombia, this paper argues that ethical review processes lack adequate consideration of ongoing ethical issues after fieldwork in conflict-affected environments, especially regarding contact with former insurgents. In addition, I argue that the tension between demands for transparency and adequately protecting both participants and researchers creates a disincentive to have open conversations about these dilemmas—especially among junior scholars.